2021
DOI: 10.3390/polym13010147
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Conductivity of Epoxy Composites Filled with Al2O3/Boron Nitride Hybrids for Underfill Encapsulation Materials

Abstract: In this study, a thermal conductivity of 0.22 W·m−1·K−1 was obtained for pristine epoxy (EP), and the impact of a hybrid filler composed of two-dimensional (2D) flake-like boron nitride (BN) and zero-dimensional (0D) spherical micro-sized aluminum oxide (Al2O3) on the thermal conductivity of epoxy resin was investigated. With 80 wt.% hybrid Al2O3–BN filler contents, the thermal conductivity of the EP composite reached 1.72 W·m−1·K−1, increasing approximately 7.8-fold with respect to the pure epoxy matrix. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…The ever-increasing device density on the printed circuit board would accordingly increase heat accumulation, which has an important impact on the performance, reliability, and service life of electronic products . Therefore, it is highly desirable to develop circuit substrates and electronic packaging materials with excellent heat dissipation capacity. , Owing to the combination of excellent adhesive capacity, dimensional stability, chemical resistance, and processability, epoxy resins have been widely used as integrated circuit substrates, electronic packaging materials, and insulating adhesives in the electronic industry. , However, the inherent thermal conductivity of neat epoxy resins is lower than 0.2 W m –1 K –1 , which incredibly limits their applications as electronic materials …”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing device density on the printed circuit board would accordingly increase heat accumulation, which has an important impact on the performance, reliability, and service life of electronic products . Therefore, it is highly desirable to develop circuit substrates and electronic packaging materials with excellent heat dissipation capacity. , Owing to the combination of excellent adhesive capacity, dimensional stability, chemical resistance, and processability, epoxy resins have been widely used as integrated circuit substrates, electronic packaging materials, and insulating adhesives in the electronic industry. , However, the inherent thermal conductivity of neat epoxy resins is lower than 0.2 W m –1 K –1 , which incredibly limits their applications as electronic materials …”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the carbonized skeleton could more effectively construct the heat conduction path. Furthermore, to demonstrate the superiority of our 3D BN/C/EP composites, the epoxy composites prepared in this work had better thermal management properties compared to previously reported polymer composites filled with boron nitride and its derivatives, as shown in Figure d. , More information is provided in Table S3.…”
Section: Resultsmentioning
confidence: 69%
“… 148 Moreover, Sanchez et al obtained a thermal conductivity of 0.22 W m −1 K −1 for pristine epoxy (EP) and further investigated the effect of a hybrid filler composed of zero-dimensional (0D) spherical micro-sized aluminum oxide (Al 2 O 3 ) and 2D flake-like hBN. 149 Ren et al placed Sb 2 S 3 NPs on highly crumpled Ti 3 C 2 T x nanosheets using the wet chemical reaction. The evenly distributed Sb 2 S 3 NPs resolved the restack issue of the Ti 3 C 2 T x nanosheets upon repetitive charging/discharging cycles, producing rich voids for rapid electron/Na + transport and reducing the volume expansion effect from Sb 2 S 3 .…”
Section: Applications Of 2d Materials and Their Compositesmentioning
confidence: 99%